SONOVOLTAMMETRY - HETEROGENEOUS ELECTRON-TRANSFER PROCESSES WITH COUPLED ULTRASONICALLY INDUCED CHEMICAL-REACTION - THE SONO-EC REACTION - Compton, R; Eklund, J; Page, S (1995)
The reduction of the ferricyanide anion, [Fe(CN)6]3-, was studied in aqueous solution at macro- and microelectrodes in the presence and absence of ultrasound directed onto the electrode surface from a sonic horn (20 kHz) located a short distance above it. Under conditions of insonation the reduction wave is seen to shift anodically when appropriate corrections for thermal effects are made. This is attributed to the reaction of the electrogenerated ferrocyanide anion with hydroxyl radicals, OH•, derived from the ultrasonically induced decomposition of the solvent, so that the electrode process is of the EC mechanistic type. This is confirmed by quantitative measurements of the potential shift as a function of the mean diffusion layer thickness as revealed by the magnitude of the transport limited current in the presence of ultrasound of constant power. © 1995 American Chemical Society.